Search
Ask a question
0

How do you simplify v(180m^4) - m^2 v125 + 2mv147m - v(75m^3) ?

a) √(180m^4) - m^2 √125 + 2m√147m - √(75m^3)
 
 
Thank you highly in advance
 

1 Answer by Expert Tutors

Tutors, sign in to answer this question.
Vivian L. | Microsoft Word/Excel/Outlook, essay composition, math; I LOVE TO TEACHMicrosoft Word/Excel/Outlook, essay comp...
3.0 3.0 (1 lesson ratings) (1)
1
Hi Lars;
a)
√(180m4) - m2√125 + 2m√147m - √(75m3)
Let's look at the numbers...
180=(36)(5)
125=(25)(5)
147=(49)(3)
75=(25)(3)
Let's rewrite the equation...
√[(36)(5)m4] - m2√(25)(5) + 2m√(49)(3)m - √[(25)(3)m3]
6m2√5 - 5m2√5 + 14m√3m - 5m√3m
m2√5 + 9√3m
 
 

Comments

I FORGOT ABOUT THE SECOND EQUATION!  SORRY!
b) √(96y3) + 2y √(384y) - √(150y3)
96=(16)(6)
384=(64)(6)
150=(25)(6)
√(16)(6)y3  + 2y√[(64)(6)y] - √[(25)(6)y3]
4y√6y + 16y√6y - 5y√6y
15y√6y